尿酸の傍細胞経路による輸送の分子メカニズム - 櫻井, 裕之; 塚田, 愛; 大槻, 純男; 市田, 公美; 福冨, 俊之; 木村, 徹 (日本薬理学会年会要旨集, 2019)
Since charged molecule cannot permeate cell membrane, urate movement across the epithelial cell layer has to be transcellularly by carrier or endocytosis/exocytosis, or paracellularly. We have reported that the paracellular route is the major urate transport pathway across the blood-placental barrier. In this study, the mechanism of urate paracellular transport was investigated in several epithelial cell lines. Very little urate passed through MDCK and LLC-PK1 cell layers. Interestingly, one Caco-2 cell line was urate non-permeable while another Caco-2 cell line was found to be urate-permeable. Urate paracellular movement across the Caco-2 cell layer was partially inhibited by DIDS, which inhibits chloride transport. Detection and quantification of claudin proteins that are important for paracellular transport of ions were performed by LC/MS. Claudin 1, 3, 4, 6, 7 and 12 were detected in urate-permeable cell lines, BeWo and Caco-2 cells. However, overexpression of these claudins in MDCK cells did not increase urate paracellular transport. In conclusion, overexpression of single claudin was not sufficient to make urate-non-permeable cell become urate permeable.